2018
DOI: 10.1016/j.drugpo.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C care continuum and associated barriers among people who inject drugs in Chennai, India

Abstract: Residual gaps in HCV knowledge and continuing negative perceptions related to interferon-based therapy highlight the need to scale-up educational initiatives. Readiness for HCV treatment was particularly low among HIV/HCV co-infected and older PWID, emphasizing the importance of tailored treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Historically, there has been a large translational gap in the delivery of treatment to the target population of PWID with HCV: prior studies from the pre-DAA era in the U.S. demonstrate that <10% of PWID have been treated (Carey et al, 2016;Mehta et al, 2008). Data on HCV care continuum among PWID in the DAA-era are emerging from around the globe (Boucher et al, 2018;Iversen et al, 2017;Mohamed et al, 2018;Patel et al, 2018;Young et al, 2018); however, to date U.S. based studies are lacking. The "care continuum" framework, which has been used for overlapping diseases such as HIV (Gardner et al, 2011;Mugavero et al, 2013) and opioid use disorders (Socias et al, 2018), outlines the steps in the care so as to identify where such barriers exist.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, there has been a large translational gap in the delivery of treatment to the target population of PWID with HCV: prior studies from the pre-DAA era in the U.S. demonstrate that <10% of PWID have been treated (Carey et al, 2016;Mehta et al, 2008). Data on HCV care continuum among PWID in the DAA-era are emerging from around the globe (Boucher et al, 2018;Iversen et al, 2017;Mohamed et al, 2018;Patel et al, 2018;Young et al, 2018); however, to date U.S. based studies are lacking. The "care continuum" framework, which has been used for overlapping diseases such as HIV (Gardner et al, 2011;Mugavero et al, 2013) and opioid use disorders (Socias et al, 2018), outlines the steps in the care so as to identify where such barriers exist.…”
Section: Introductionmentioning
confidence: 99%
“…Although access to care is guaranteed to all persons with HCV, the proportion of HCV patients receiving DAA therapy in Italy remains low. The lack of HCV treatment among PWIDs in high-income countries is due to several factors [21][22][23][24][25][26][27][28][29][30][31]. Some barriers to care persist even after the advent of DAAs [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported an association between injections drug user (IDU), female sex workers (FSW), men sex with men (MSM) and HCV, and some study reported associated risk patient; β-thalassemia, visceral leishmaniasis, jaundice, dialysis, three studies combined measure 12% prevalence in pregnant women, and also reported slum population and primitive groups with 6% prevalence (Table 2). 1,4,8,[14][15][16][17][18][19]20,22,23…”
Section: Resultsmentioning
confidence: 99%